Temperature-dependent electrical properties of graphene nanoplatelets film dropped on flexible substrates. Issue 11 (9th June 2014) - Tian, Min; Huang, Ying; Wang, Weihua; Li, Ruiqi; Liu, Ping; Liu, Caixia; Zhang, Yugang
Abstract: Abstract : The fabrication of a temperature sensor based on graphene nanoplatelets (GNPs) is reported. A preheat process was carried out and the micrographs of both original and preheat-treated GNPs are observed and compared. Nonlinear temperature variation of resistance is observed and humidity interference is found to be negligible. Region of 10–60 °C (the linear region) is selected as the sensor range and further studied. High sensitivity of GNPs can be seen and the temperature coefficient of resistance (TCR) of 0.0371 is calculated, higher than that of multiwall carbon nanotubes (MWCNTs) and many other materials reported in references. Great repeatability and small hysteresis are obtained. The time constant of the GNPs film is about 5 s, much shorter than that of MWCNTs film. The result suggests that GNPs have potential applications for use in highly sensitive and fast-response temperature sensors.